The growth rate of the Japanese economy since 1878. - Ōkawa, Kazushi (Tokyo, Kinokuniya Bookstore Co., 1957)
This volume provides in detail new long-term national income figures for Japan, is a translation, revised and expanded, of a 1955 report. It is more of a historical-statistical series of Japanese economic growth, ranging from national income to capital formation, and from population to price deflators. Furthermore, all statistical techniques are carefully explained. In most instances the time period covered runs from 1878 to 1942, and in some cases post-war data are included.
lje 17/10/18
Loans
Keywords: Industries; Saving and investment; Japan